Growth And Development Of Preschool-Aged Children - Arif Rohman Mansur; Mutia Farlina (Eureka Media Aksara, 2023)
Preschool-age children are children between the ages of 3 and 6 years, during this period, physical growth slows down and psychosocial and cognitive development increases. Preschool age is calledThe Wonder Yearsnamely the period when a child has a high sense of curiosity. They are beginning to develop their curiosity and are still learning how to be friends, interact with their surroundings, control their bodies, emotions and minds and be able to communicate better. The quality of a child can be judged from the process of growth and development. The process of growth and development is the result of the interaction of genetic factors and environmental factors. Hereditary factors are factors related to genes that come from the father and mother, while environmental factors include the biological, physical, psychological and social environment. This book consists of five chapters, namely Chapter 1 Growth, Chapter 2 Development, Chapter 3 Principles of Growth and Development, Chapter 4 Fulfilling Growth and Development Needs, and finally Chapter V Anticipatory Guidance at preschool age. It is hoped that parents and caregivers will be able to understand the process of growth and development at this preschool age, fulfill the needs of preschool-aged children both in terms of biomedical physics , emotion and affection, and providing stimulation.